PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI DENGAN KESADARAN MEREK DAN PERSEPSI KUALITAS SEBAGAI VARIABEL INTERVENING (Studi pada Produk Kosmetik BLP Beauty di Kota Semarang) - Shafira Artamevia Herdita Putri; Mahfudz Mahfudz (Faculty of Economics and Business Diponegoro University, 2022)
Electronic Word of Mouth is one of the most frequently used strategy by companies to market their products. It is supported by the increasingly advanced growth of digital era and the company always make efforts to connect with customers. Thisresearch aims to analyze the influence of Electronic Word of Mouth on puchase intention through brand awareness and perceived quality as the intervening variable (a study on BLP Beauty cosmetic products in Semarang city). The variable are used in this study consisted of independent variable is Electronic Word of Mouth, 2 variable intervening such as brand awareness and perceived quality, and dependent variable is purchase intention. The samples in this research are 135 respondents of women within age of 16- 54 years old who live in Semarang city and recognize or have bought BLP Beauty cosmetic. The sampling method used in this research is non-probability sampling method with purposive sampling technique. The method of data collection is conducted through questionnaires. This research used analytical technique of Structural Equation Model (SEM) with AMOS as the analysis instrument. The result of this research show that Electronic Word of Mouth has a positive effect on brand awareness and perceived quality. Brand awareness and perceived quality has a positive effect on purchase intention. furthermore, Electronic Word of Mouth also has a positive effect on purchase intention.